2017
DOI: 10.1111/j.1564-913x.2015.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Which skills protect graduates against a slack labour market?

Abstract: This article explores the relationship between graduates' skills and their risk of over-education and unemployment in 17 European countries. Distinguishing between field-specific and academic skills, the authors find that, as predicted by the crowding-out hypothesis, field-specific skills offer more protection against the risk of over-education when the excess labour supply in the occupational domain of the graduate's field of study increases. Conversely, academic skills have that effect when excess supply in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…That each of these dimensions should not necessary have the same implications for labour market outcomes is illustrated by Dolton and Vignoles (2002), who found a strong impact of mathematics A levels on earnings but not of a broader curriculum. Similarly, Humburg et al (2015) found both analytical thinking skills and mastering one's own field to be associated with lower degrees of overeducation among graduates. Probably, each of these dimensions also have different short-run and more long-run labour market implications.…”
Section: Other Explanationsmentioning
confidence: 90%
See 1 more Smart Citation
“…That each of these dimensions should not necessary have the same implications for labour market outcomes is illustrated by Dolton and Vignoles (2002), who found a strong impact of mathematics A levels on earnings but not of a broader curriculum. Similarly, Humburg et al (2015) found both analytical thinking skills and mastering one's own field to be associated with lower degrees of overeducation among graduates. Probably, each of these dimensions also have different short-run and more long-run labour market implications.…”
Section: Other Explanationsmentioning
confidence: 90%
“…First, the bulk of the research on the labour market effects of vocationally oriented programs focuses on secondary education. Studies focussing on tertiary education graduates remain scant (Giret 2011;Verhaest and Van der Velden 2013;Humburg et al 2015) and, hence, more research is needed to reassure that the aforementioned conclusions also apply to them. At least, a recent study by Brunello and Rocco (2015) suggests that the labour market effects of more vocationally oriented programs are less favourable in the case of tertiary than in the case of secondary education.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated: (a) the average reduction in the employment rate and earnings in individuals after the onset of first recorded sickness absence due to MDD, (b) whether individuals with sickness absence due to MDD have lower employment rate and earnings before the first MDD-related sickness absence, (c) whether the association between MDD and employment differs according to the severity of MDD and duration of sickness absence related to MDD, (d) whether associations were similar in all educational groups. The heterogeneity analysis is important because high education may protect individuals from loss of earnings 30 . Depression diagnoses and reporting of depressive symptoms are more common in women than in men 31 , although previous studies have provided mixed empirical findings whether the association between MDD and socioeconomic factors differs between men and women 29,32,33 .…”
Section: How Might This Impact On Policy or Clinical Practice In The Foreseeable Future?mentioning
confidence: 99%
“…In the age of technological advances, graduates are the most valued source of labour force for any employers. While many studies have been conducted to assess skills and readiness of graduates to enter the job market, recent focuses are on skills demand and modern job market requirements (Figueiredo et al, 2017;Humburg et al, 2017;Matsouka & Mihail, 2016). Therefore, it raises the question of what determines fresh graduates to search for jobs?…”
Section: R E S E a R C H O B J E C T I V E Smentioning
confidence: 99%